[18F]FDG-PET as an imaging biomarker to NMDA receptor antagonist-induced neurotoxicity - Shirakawa, Takafumi; Mitsuoka, Keisuke; Kuroda, Kanae; Miyoshi, Sosuke; Shiraki, Katsuhisa; Naraoka, Hitoshi; Noda, Akihiro; Fujikawa, Akihiko; Fujiwara, Michio (Toxicological sciences, 2013)
Positron emission tomography (PET) is an effective tool for noninvasive examination of the body and provides a range of functional information. PET imaging with [(18)F]fluoro-2-deoxy-d-glucose ([(18)F]FDG) has been used to image alterations in glucose metabolism in brain or cancer tissue in the field of clinical diagnosis but not in the field of toxicology. A single dose of N-methyl-d-aspartate (NMDA) receptor antagonist induces neuronal cell degeneration/death in the rat retrosplenial/posterior cingulate (RS/PC) cortex region. These antagonists also increase local cerebral glucose utilization. Here, we examined the potential of [(18)F]FDG-PET as an imaging biomarker of neurotoxicity induced by an NMDA receptor antagonist, MK-801. Using [(18)F]FDG-PET, we determined that increased glucose utilization involved the neurotoxicity induced by MK-801. The accumulation of [(18)F]FDG was increased in the rat RS/PC cortex region showing neuronal cell degeneration/death and detected before the onset of neuronal cell death. This effect increased at a dose level at which neuronal cell degeneration recovered 24h after MK-801 administration. Scopolamine prevented the neurotoxicity and [(18)F]FDG accumulation induced by MK-801. Furthermore, in cynomolgus monkeys that showed no neuronal cell degeneration/death when treated with MK-801, we noted no differences in [(18)F]FDG accumulation between test and control subjects in any region of the brain. These findings suggest that [(18)F]FDG-PET, which is available for clinical trials, may be useful in generating a predictive imaging biomarker for detecting neurotoxicity against NMDA receptor antagonists with the same pharmacological activity as MK-801.